Incidence of Undiagnosed Celiac Disease Presenting as Bone Stress Injuries to a Sport and Exercise Medicine Clinic. Issue 6 (November 2021) - Smith, Ralph; Baldock, James; FitzPatrick, Michael; Jones, Natasha; Newton, Julia L.
Abstract : Objective: To evaluate the incidence of undiagnosed celiac disease (CD) in patients presenting with bone stress injuries (BSI) to a NHS Sport and Exercise Medicine (SEM) clinic. Design: Retrospective cohort study. Setting: Single tertiary-level SEM clinic. Patient/Participants: One hundred consecutive patients with radiologically proven BSIs. Interventions: Laboratory blood tests (LBT) can unmask underlying metabolic bone disorders. Anti-tissue transglutaminase antibody (TTG) testing has a high sensitivity and specificity for CD. In this SEM clinic, clinicians were encouraged to perform LBT including TTG, at time of diagnosis of BSI. A retrospective analysis of age, sex, fracture site, co-morbidities, TTG result, and subsequent investigations was performed. Main Outcome Measures: The primary outcome was the number and percentage of patients with BSIs and either positive TTG (CD seropositivity) or a diagnosis of CD. Results: Of the 100 patients with radiologically proven BSIs, 70% were female, and the mean age was 37 years (range 16-69). Eighty-five percent had the appropriate LBTs, of which 70% (60/85) were female, and the mean age was 37(16-69). Metatarsal (35%) and tibial (21%) were the most common BSIs. Anti-tissue transglutaminase antibody was performed in 85 patients. Two patients (2/85) had pre-existing CD and were excluded from incidence calculations. Five patients [5/83 (6%), mean age 38 years (28-57), 80% female] had a positive TTG, of whom 3 have subsequently had CD confirmed by endoscopic biopsy. Four patients with a positive TTG underwent dual-energy X-ray absorptiometry with osteopenia found in 3 (75%) cases. Conclusions: In this cohort, the incidence of CD seropositivity was 6%, and the prevalence of biopsy-confirmed CD was 5%, approximately 5-fold higher than UK population estimates. Anti-tissue transglutaminase antibody screening for CD should be considered in all patients presenting with BSIs.